A Shear Mixing approach in Polymer Composite Formation - Ayub, S. (Institute of Electrical and Electronics Engineers Inc., 2021)
Over time, a variety of composites are formed at the research and industrial level where not all the time the results are in favour. Various reasons exist in the formation of a composite in which the role of revolutions per minute (RPM) is one of them. Therefore, the aim of this research is to explore the impact of RPM in making the composite. For this purpose, multi-layer graphene (MLG) and polydimethylsiloxane (PDMS) was taken to formed two composites, in which one was prepared by adding the ethanol in MLG and later mixed with PDMS, and the other was prepared by direct mixing of MLG with PDMS. The physical and experimental inspection was made where the results reveal that a unique dispersion was achieved at low RPM in the first sample. However, the FTIR analysis revealed a less existence of MLG in both the formed composites. Although the low RPM speed was kept at 100, still less MLG sign was visible in the sample. Therefore, a further investigation is required to observe the loss phenomena of MLG within the composites due to the RPM speed. Â© 2021 IEEE.